2020
DOI: 10.1002/smll.201904322
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Anomalous Hall Effect in Magnetic Doped Topological Insulators and Ferromagnetic Spin‐Gapless Semiconductors—A Perspective Review

Abstract: between intrinsic magnetization and spin-orbit coupling (SOC). Unlike spindegenerate chiral edge states in integer quantum Hall effect where time-reversal symmetry (TRS) is broken through external magnetic field, the trademark of QAH effect is the spinless/spinful chiral edge states. Such macroscopic quantum phenomenon, originating from the bulk topology of QAH systems, is ideal for transport in both electronics and spintronics devices. After seminal proposal by Haldane, [1] a number of theoretical models were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 114 publications
0
21
0
Order By: Relevance
“…[1] The idea to combine ferromagnetism with topological insulators for this purpose [2][3][4] has fuelled the materials science. [5,6] It led to the experimental discovery of the QAHE in Cr-and V-doped (Bi, Sb) 2 Te 3 [7][8][9][10][11] with precise quantized values of the Hall resistivity down to the sub-part-per-million level. [12][13][14][15] The stable 3+ configuration of V or Cr substitutes the isoelectronic Bi or Sb [3,16,17] enabling ferromagnetism by coupling the magnetic moments of the transition metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The idea to combine ferromagnetism with topological insulators for this purpose [2][3][4] has fuelled the materials science. [5,6] It led to the experimental discovery of the QAHE in Cr-and V-doped (Bi, Sb) 2 Te 3 [7][8][9][10][11] with precise quantized values of the Hall resistivity down to the sub-part-per-million level. [12][13][14][15] The stable 3+ configuration of V or Cr substitutes the isoelectronic Bi or Sb [3,16,17] enabling ferromagnetism by coupling the magnetic moments of the transition metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In passing, it is noted and will be be presented in a separate study, longitudinal momentum and width dependence of gate-induced inter-edge coupling can also be employed to tune the exchange interaction in 2D magnetic topological insulators. [49][50][51][52][53][54][55][56][57] For example, critical regime in an antiferromagnetic topological insulators can be optimized to design a topological spin transistor via gate induced topological switching of edge state spin transport.…”
Section: Discussionmentioning
confidence: 99%
“…Topological physics is flourishing as an active field, which has drawn extensive attention in both fundamental research and applied science [1]. Topological insulator commonly features the striking phenomenon of topologically protected one-way transport, exhibiting edge states or surface states that are strongly robust against defects, disorders, obstacles, sharp corners and so on [2,3]. Inspired from the discovery of condensed quantum Hall effect, many studies have shown that topological states show essentially single-particle behavior of electrons and one can establish an analogy relationship with photon behaviors called topological photonic state (or topological one-way edge state) [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%